Physical and shielding properties of Er2O3 rare earth oxide compound content on PCL/PEG blend - Tasgin, Yahya; Pekdemir, Mustafa Ersin; Yilmaz, Mucahit; Kanca, Muhammed Sait; Kok, Mediha (Springer, 2024)
Rare earth elements (RRE), due to their unique magnetic, electrical, and optical properties, are an important group of elements demanded in many application areas from machine technology to the health industry. In this study, new composites were obtained by mixing Erbium oxide (Er2O3), one of the rare earth element oxides, into PCL-PEG blend, which is also an important material group, in different ratios. The characteristic functional groups of the obtained polymer blend/Er2O3 nanocomposites were determined by the ATR-IR, and as the erbium oxide ratio increased, characteristic peaks of the polymers in the blend as well as characteristic signals of the Er-O-Er bond were found. When the thermal behavior of the obtained composites was examined, it was observed that the polymer blend exhibited miscible blend properties and the melting temperature of the polymer blend increased as the Er2O3 ratio increased. In addition, it was determined that the thermal stability of the composite increased significantly. X-ray measurements of composites at room temperature support other measurement results. It was determined that the presence of Er-RRE oxide increased the crystal structure feature in the polymer blend composite. Gamma radiation shielding capabilities of polymer materials containing different erbium ratios were investigated by calculating shielding parameters such as half value layer (HVL), radiation protection efficiency (RPE), and mean free path (MFP). Cs-137 and Co-60 radioactive sources were used as gamma sources. According to the obtained measurement results, Erbium oxide increased the absorption property of the polymer composite material. [GRAPHICS] .
Keywords: Rare earth element; Polymer blends; Composite; Thermal stability; Radiation shielding